Chloride intracellular channel (CLIC) proteins function as fusogens - Bar Manori; Alisa Vaknin; Pavla Vaňková; Anat Nitzan; Ronen Zaidel-Bar; Petr Man; Moshe Giladi; Yoni Haitin (Nature Communications, 2024)
Abstract Chloride Intracellular Channel (CLIC) family members uniquely transition between soluble and membrane-associated conformations. Despite decades of extensive functional and structural studies, CLICs’ function as ion channels remains debated, rendering our understanding of their physiological role incomplete. Here, we expose the function of CLIC5 as a fusogen. We demonstrate that purified CLIC5 directly interacts with the membrane and induces fusion, as reflected by increased liposomal diameter and lipid and content mixing between liposomes. Moreover, we show that this activity is facilitated by acidic pH, a known trigger for CLICs’ transition to a membrane-associated conformation, and that increased exposure of the hydrophobic inter-domain interface is crucial for this process. Finally, mutation of a conserved hydrophobic interfacial residue diminishes the fusogenic activity of CLIC5 in vitro and impairs excretory canal extension in C. elegans in vivo. Together, our results unravel the long-sought physiological role of these enigmatic proteins.